XML WEB SERVICE SEBAGAI MIDDLEWARE PADA EXISTING SERVICE - Rismanto, Ridwan (DINAMIKA DOTCOM, 2015)
One of the characteristic of a good system is, flexibility in term of accessibility. In an attempt to acquire this characteristic, a system must be built based on loosely coupled concept. This concept will enable a particular system to be accessed in any platform regardless of what platform the main system was built. In our previous research, we have built a system to enable student of State of Polytechnic Malang to do their registration and study planning. However, this system is tightly integrated which made it impossible to access any of the functionality and data from outside the system itself. In this research, we will build a middleware to conforms this restriction. We will use the Web service technology to acquire such feature. Our top-down method has been proved to increase the flexibility of this system without altering the main system at all, while still maintain the security credentials aspect of the system itself.Â Keywords : SOAP, WSDL, Web Service, daftar ulang, perencanaan studi, middleware, ASP.NET